PENDAMPINGAN PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI SECARA DARING BAGI GURU-GURU SEKOLAH DASAR KELAPA NUNGGAL DI DESA SUKA MAKMUR KABUPATEN BOGOR JAWA BARAT - Dudung Amir Soleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract The global pandemic that occurred in Indonesia made many parties take part in overcoming it. The pandemic caused by the Coronavirus caused many impacts in Indonesia. One of the impacts of the Coronavirus 2019 (COVID-19) pandemic is on education around the world. The government is trying to overcome the impacts that arise from this pandemic by implementing a distance learning system. Evaluation of online IT-based learning is a form of remote system evaluation. In order to help distance learning and improve the quality of student learning outcomes online, the author will conduct community service on teacher assistance in designing, developing and processing evaluations of online IT-based learning. This community service will be held at Kelapa Nunggal Elementary School, Kelapa Nunggal District, Bogor Regency. This activity aims to provide solutions to partner schools in the learning evaluation process. With this service activity, it is hoped that teachers can design, implement and process in the evaluation process of online IT-based learning, so that evaluations are more effective, interesting and fun. The steps for this service activity are 1. Initial evaluation to see the analysis of the needs of conditions in the field regarding the implementation of learning evaluations carried out by teachers. 2) Conduct training and assistance in developing IT-based learning evaluation, namely the Kahoot, Quiziz and Mentimeter applications. 3) The final evaluation stage is carried out by distributing questionnaires about satisfaction and understanding of the training materials. The results of the evaluation showed very high enthusiasm and understanding from all participants, elementary school teachers in Kelapa Nunggal District. 3) The final evaluation stage is carried out by distributing questionnaires about satisfaction and understanding of the training materials. The results of the evaluation showed very high enthusiasm and understanding from all participants, elementary school teachers in Kelapa Nunggal District. 3) The final evaluation stage is carried out by distributing questionnaires about satisfaction and understanding of the training materials. The results of the evaluation showed very high enthusiasm and understanding from all participants, elementary school teachers in Kelapa Nunggal District. Abstrak Pandemi global yang terjadi di Indonesia membuat banyak pihak ikut berperan dalam mengatasinya. Pandemi yang disebabkan oleh Coronavirus menyebabkan banyak dampak di Indonesia. Salah satu dampak pandemi Coronavirus 2019 (COVID-19) ialah terhadap pendidikan di seluruh dunia. Pemerintah berupaya untuk menanggulangi dampak yang muncul dari pandemi ini dengan cara menerapkan sistem pembelajaran jarak jauh. Evaluasi Pembelajaran berbasis IT secara daring salah satu bentuk evaluasi system jarak jauh. Dalam rangka membantu pembelajaran jarak jauh dan meningkatkan kualitas hasil pembelajaran siswa secara daring, penulis akan mengadakan pengabdian masyarakat tentang pendampingan guru dalam merancang, mengembakan serta mengolah evaluasi pembelajaran berbasis IT secara daring. Pengabdian masyarakat ini akan diadakan SD Kelapa Nunggal Kecamatan Kelapa Nunggal Kabupaten Bogor. Kegiatan ini bertujuan untuk memberikan solusi kepada sekolah mitra dalam proses evaluasi pembelajaran. Dengan adanya kegiatan pengabdian ini, diharapkan guru dapat merancang, melaksanakan dan mengolah dalam proses evaluasi pembelajaran berbasis IT secara daring, agar evaluasi lebih efektif, menarik dan menyenangkan. Langkah kegiatan pengabdian ini adalah 1. Evaluasi awal untuk melihat analisis kebutuhan konsdidi dilapangan tentang pelaksanaan evaluasi pembelajaran yang dilakukan oleh para guru. 2) Melakukan pelatihan dan pendampingan dalam mengembangkan evalasi pembelajaran berbasis IT yaitu aplikasi Kahoot, Quiziz dan mentimeter. 3) Tahap evaluasi akhir dilakukan dengan menyebarkan angket tentang kepuasan dan keterpahaman terhadap materi pelatihan. Hasil evaluasi menjukan antusime dan keterpahamna yang sangat tinggi dari seluruh peserta guru-guru Sekolah Dasar Kecamatan Kelapa Nunggal